TINGKAT KECEMASAN PADA SISWA KELAS XII SMA NEGERI 5 AMBON DALAM MENGHADAPI UJIAN NASIONAL - Walasary, Sammy A.; Dundu, Anita E.; Kaunang, Theresia (e-CliniC, 2015)
Abstract: National examination is held to evaluate the competence of Indonesian students after they have finished any formal education level. There is a chance of growing number of students that fail in the examination. Therefore, it becomes an important issue that leads to anxiety among Indonesian students. This study aimed to obtain the anxiety level among SMAN 5 Ambon students facing the national examination. This was a descriptive cross-sectional study design using socio-demographic questionnaire and Hamilton anxiety rating scale (HARS). Most of respondents had mild (51.3%) and moderate (40%) level of anxiety. Conclusion: Anxiety was common among groups of students aged 17 and female. Keywords: anxiety, national examination, Hamilton anxiety rating scale(HARS) Abstrak:Ujian nasional bertujuan untuk menilai dan mengukur kompetensi peserta didik secara nasional dilaksanakan setelah mengikuti pembelajaran yang diberikan para guru pada pendidikan formal. Salah satu isu yang marak diperbincangkan ialah kekhawatiran tentang kemungkinan banyaknya siswa yang tidak lulus, hal ini akan memicu kecemasan siswa. Penelitian ini bertujuan untuk mengetahui tingkat kecemasan siswa Sekolah Menengah Atas Negeri 5 Ambon dalam menghadapi ujian nasional. Penelitian ini bersifat deskriptif dengan desain potong lintang. Pengumpulan data dilakukan dengan menggunakan kuesioner data sosiodemografik dan Hamilton anxiety rating scale (HARS). Sebagian besar responden berada pada kategori kecemasan tingkat ringan (51,3%) dan sedang (40%) dalam menghadapi ujian nasional. Simpulan: Kecemasan paling banyak dialami kelompok umur 17 tahun dan jenis kelamin perempuan. Kata kunci: kecemasan, ujian nasional, Hamilton anxiety rating scale (HARS)